Performatividade e cinema contemporâneo: procedimentos nas extremidades em Gabriel Mascaro - Silva, Katrin Riato (2020)
This dissertation seeks to produce a reflection on the performativity of the subjects and the image, through the study of contemporary Brazilian cinema. The corpus of the research is the film Avenida Brasília Formosa, by the director and visual artist Gabriel Mascaro (Recife, PE, 1983). It also addresses the performativity of the subjects before the cameras through the concept of performative persona, the convocation of the body and affections in the audiovisual, the biopolitics of everyday life and the post-colonialist production as a rupture of a unique narrative in cinema. the tensions of cinema with other languages in this work; and which procedures of the film signal a constitution of the contemporary subject and its performances. The theoretical structure has an interdisciplinary character, since it is a reading that is located in the tensions of cinema with other languages and with phenomena that destabilize the cinema form, such as the presence o f the language of video performance, hybridizations between amateur and professional image and the collaborative mode of production characterized by the phenomenon of budding. At first, we seek to understand audiovisual policy in Recife and collaborative networks from Amanda Custódio Nogueira; micropolitical relations and daily life from Michel de Certeau and Tarcisio Torres Silva; the context of post-industrial cinema and immaterial and cognitive capitalism in the analyses of Cezar Migliorin, Jean-Louis Comolli, Maurizio Lazzarato, Ilana Feldman and Vladimir Safatle; and the post-colonialist positioning on the symbolic plane from Moacir dos Anjos, Suely Rolnik and the manguebeat movement. In a second moment, it approaches the various crossings and hybridizations of the work through the vectors of deconstruction, contamination and sharing of Christine Mello's approach to the ends, which comprises a subversion of the immersion regime in the cinema room, hybridizations of cinema with performance, video performance, reality show, network and graphic language of the video game and the dissolution of the hierarchy in the production processes in the cinema; and the constitution of the presence through the real-time concept of Arlindo Machado. Finally, there is the approximation between performance and cinema, analyzing the construction of the performative persona through Ana Goldenstein Carvalhaes and Renato Cohen; readings of performance as a center of audiovisual production from André Brasil; the idea of fabulation of Gilles Deleuze; and a trajectory of film performance